A comparative proteomic study of cold responses in potato leaves. Issue 2 (February 2021) - Li, Huawei; Luo, Wenbin; Ji, Rongchang; Xu, Yongqing; Xu, Guochun; Qiu, Sixin; Tang, Hao
Abstract: The potato is an important food crop worldwide. While potatoes are rich in nutrition, the production suffers from yield loss caused by frost and freezing. This study used a common potato cultivar, 'Zhengshu 6', as the study system to measure the changes in the contents of soluble protein, malondialdehyde (MDA), proline, and chlorophyll after 1, 3, 5, and 7 days of low temperature treatment. We performed two-dimensional electrophoresis (2-DE) in combination with liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) technology and identified 52 differentially expressed protein spots among these timepoints. Results showed that levels of soluble protein, MDA, and proline increased as the duration of the low temperature treatment increased, and the chlorophyll content decreased. The 52 identified protein spots were classified by function as involved in defense response, energy metabolism, photosynthesis, protein degradation, ribosome formation, signal transduction, cell movement, nitrogen metabolism, and other physiological processes, thus allowing potato plants to achieve metabolic balance at low temperatures. Abstract : potato; proteomics; low temperature stress; differentially expressed.